Photometric measurement for LED roadway lighting at Kuala Lumpur – Karak Expressway - Mohd Nasir, Mohamad Na'im; Sulaima, Mohamad Fani; Jaafar, Hazriq Izzuan; Ramani, Anis Niza; Wan Abdul razak, Intan Azmira (2013)
This paper presents the measurement of photometric measurements of LED lighting at Kuala Lumpur - Karak Expressway. The aim of this paper is to comply the photometric quantities of LED roadway lighting with International Commission on Illumination (CIE) standard and Lembaga Lebuhraya Malaysia (LLM) requirement. This paper has focused on testing procedure for photometric measurement for LED roadway lighting. The DIALux software is used for lux calculation which in turn will assist in all the photometric calculations. It has been proved that the results were complied with CIE standard and LLM requirement.